Irritant compounds: aldehydes - Patočka, Jiří; Kuča, Kamil (Vojenské zdravotnické listy, 2014)
Many aldehydes are respiratory irritants which can cause inflammation or other adverse reactions in the respiratory system after being inhaled. Depending on the type and amount of irritant compound inhaled, victims can exhibit symptoms ranging from minor respiratory discomfort to acute airway and lung injury and even death. The lungs are susceptible to many airborne irritants. There are hundreds of substances that can pollute air and harm lungs. Aldehydes are just one type of airborne pollutants that can adversely affect lungs. Some of these agents may be directly toxic. They are also strong irritants for the skin, eyes, and nasal passages. The vapor is irritating to the eyes and respiratory tract. Aldehydes as acrolein or glutaraldehyde are also corrosive substances.
Keywords: Benzaldehydes; Formaldehyde; Irritants; akrolein; acetaldehyd; glutaraldehyd; Glutaral; Aldehydes; Air Pollution; Malondialdehyde; králíci; benzaldehydy; aldehydy; krysa rodu Rattus; poruchy dýchání; Acrolein; Respiration Disorders; formaldehyd; znečištění ovzduší; lidé; Animals; Humans; zvířata; malondialdehyd; Rats; Rabbits; myši; dráždivé látky; Acetaldehyde; Mice